2019
DOI: 10.4314/njt.v38i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Air quality assessment of some oil facilities host communities in Rivers State

Abstract: The study evaluated air quality around host communities of oil companies in Ogba/Egbema/Ndoni Local Government Area in Rivers state. Detailed literature reviews and appropriate multi-gas observing instruments were utilized to obtain air quality information. Results of SO 2 in Omoku, Obrikum, Ebocha land Control (5km) from Oil Company indicated 214.1µg/m 3 , 0µg/m 3 , 71.4µg/m 3 and 28.5µg/m 3. NO 2 was 106µg/m 3 , 0.0µg/m 3 , 51,3µg/m 3 and 0.0µg/m 3 respectively. CH 4 was 98,120µg/m 3 , 35,680µg/m 3 and 44600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is also similar to findings reported in a study conducted to assess the air quality of host communities to some Nigerian oil exploration companies who are exposed to crude oil pollution. The study revealed that higher concentrations of toxic pollutants were found in the air in oil polluted communities especially hydrocarbon, carbon monoxide, nitrogen dioxide, and PM2.5 which exceeded the NAAQS limits [33].…”
Section: Discussionmentioning
confidence: 89%
“…It is also similar to findings reported in a study conducted to assess the air quality of host communities to some Nigerian oil exploration companies who are exposed to crude oil pollution. The study revealed that higher concentrations of toxic pollutants were found in the air in oil polluted communities especially hydrocarbon, carbon monoxide, nitrogen dioxide, and PM2.5 which exceeded the NAAQS limits [33].…”
Section: Discussionmentioning
confidence: 89%